Synthesis, Spectral Characterization and Biological Evaluation of Glutaric acid based Macrocyclic Complexes - Rajrani gulia, Rajrani Gulia; Vikas Sangwan, Vikas Sangwan; Anshul, Anshul Singh (Asian Journal of Chemistry, 2023)
In the presence of divalent transition metal ions in their chloride forms, glutaric acid and o-phenylenediamine were used to design and synthesize a unique series of macrocyclic complexes. The UV-Visible, IR, ESR, and ESI-MS spectroscopy methods were used to analyze these newly designed complexes. In order to evaluate their thermal behavior, TGA analysis was employed. The intended general formula for the produced complexes was [M(L)X2] (L = ligand, X = Cl- and M = Co2+, Ni2+ and Cu2+). The central metal ions are surrounded by octahedral environment. These macrocyclic complexes were tested for their antimicrobial effectiveness against the selected bacterial strains (Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Escherichia coli), as well as fungi strains (Aspergillus niger and Candida albicans) and their efficacy was compared to that of standard drugs Streptomycin and Itraconazole respectively. Moreover, the antioxidant activity of the macrocyclic complexes were also assessed using the DPPH assay.